Who’s Got the Power: Systems, Culture, and Influence in Higher Education Change Leadership - Terron J. Phillips; Lisa Lambert Snodgrass (Journal of Higher Education Policy and Leadership Studies, 2022)
American higher education has managed to maneuver monumental periods of seismic change throughout the country’s history. Recent demographic, political, and ideological shifts within the internal and external environments of higher education indicate that the field is approaching yet another significant period of change; one that could require institutions to undergo significant structural and cultural redesign. The literature on change leadership and organizational theory suggests that those in senior-level leadership roles at institutions are often best positioned to encourage, implement, and lead change initiatives. But what are the actual lived experiences of senior administrators during change processes at the individual, institutional, and spherical level in higher education? This qualitative study examines the experiences of six senior-level administrators at American higher education institutions during periods of internal and external change. The participants described how internal and external factors impacted their perceived influence in implementing, and leading structural and cultural change at various levels within the field. Future studies might consider an examination of the practical influence and/or preparedness of higher education leaders to guide forecasted change initiatives within the field.